Validation of a dual in vivo–in vitro assay for predicting the digestibility of nutrients in humans. (2nd April 2013) - Coles, Leah T; Moughan, Paul J; Awati, Ajay; Darragh, Alison J
Abstract: Background: The validation of a dual in vivo–in vitro digestibility assay ('dual digestibility assay') for separately predicting the upper‐tract, hindgut and total tract digestibility of nutrients in humans, as estimated using organic matter digestibility (OMD), is described. Human upper‐tract OMD was predicted using an animal (rat) model with digesta from the terminal ileum collected from rats fed one of four complete human diets (wheat bran diet, pectin diet, mixed low‐fibre diet, mixed high‐fibre diet). Large intestinal OMD was predicted using an in vitro hindgut fermentation assay employing a human faecal inoculum and with the rat ileal digesta as the substrate . Results: A comparison of total tract OMD of the four diets from a human balance study (OMDhuman ) with that predicted using the dual digestibility assay (OMDdual ) showed no significant differences ( P > 0.05). OMDhuman and OMDdual were highly correlated ( r = 0.953, P = 0.047) . Conclusion: The dual digestibility assay accurately predicts the uptake of dietary nutrients (as grams of organic matter) in humans over the total tract. The assay is able to separately quantify the digestibility of nutrients in the upper and lower digestive tracts. The validation of the dual digestibility assay needs to be extended to a wider range of human diets. © 2013 Society of Chemical Industry